Analysis of the socio-economic impacts of Jatigede reservoir development on the Wado village community in Sumedang regency - Andini, Febby; Winarno, Winarno; Fadiarman, Fadiarman (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Climate change impacts changes in water availability for agricultural activities and water supply for household needs. Many regions in Indonesia and especially in West Java are already limited by the amount and quality of available water. Freshwater ecosystem are vulnerable to climate change and build reservoir is one of the solutions for water supply.  This research analyzes the impact of the Jatigede reservoir inundation on the Wado Village community, including changes in population, education, employment, income, economic growth, and social community. The reservoir was built to overcome flooding in Indramayu and support irrigation in Cirebon and surrounding areas. Using a purposive sampling method, the study found a decline in community income with a sharp drop between 2022 and 2023. Proposed solutions include community empowerment, local infrastructure investment, and development of sectors such as tourism, agriculture, and fisheries to create employment opportunities. Socially, the relocation of residents led to changes in communication patterns, with houses now far apart. The implications of the research show significant economic and social impacts, such as the need for skills upgrading and job stability, as well as investment in local sectors. Inclusive and participatory approaches to development are also needed to enable communities to adapt to the social changes brought about by relocation.